A large ureteric calculus: is there a role for open surgery in the modern era? - Maranna, Haraesh; Hameed, Tariq; Lal, Pawan (International Surgery Journal, 2019)
A 36 year old gentleman presented with recurrent urinary tract infections, hematuria and lump in the left side of abdomen for 4 months. Clinically a soft, non-tender lump in left lumbar region with well-defined margins was palpable. CT scan of abdomen revealed a calculus of size 45 mm at the left vesico-ureteric junction with gross left hydronephrosis. Patient underwent open ureterolithotomy in view of the large size of calculus and due to stone impaction. Post-operative period was uneventful. Patient was followed up for 6 months and remained asymptomatic.